渐开线齿形样板计算软件的设计与分析 - 游朝阳; 王宽伟; 蔡爱民; 李英姿; 李克诚 (Jixie chuandong)
According to the theory of forming process,the involute gear tooth profile is used to design the profile of finger cutter and disc cutter. Calculation of involute gear tooth profile is always used during the machining process. After analyzing the calculating process of involute gear tooth profile,based on Microsoft Office Excel 2003,the design of the calculating software of involute gear tooth profile is developed,and it’s useful to the gear manufacturing.